2012
DOI: 10.1007/s00216-012-5809-x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of dynamic change in contraction-induced lipid composition in mouse skeletal muscle by matrix-assisted laser desorption/ionization imaging mass spectrometry

Abstract: Lipids in skeletal muscle play a fundamental role both in normal muscle metabolism and in disease states. Skeletal muscle lipid accumulation is associated with several chronic metabolic disorders, including obesity, insulin resistance, and type 2 diabetes. However, it is poorly understood whether the lipid composition of skeletal muscle changes by contraction, due to the complexity of lipid molecular species. In this study, we used matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI-IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…An example of such extended ratio analysis is visualization of energy charge, which was introduced to characterize metabolic energy state using number of phosphorylation sites calculated from abundance of ATP, ADP, and AMP. 36,37) In the near future, various visualizations will be performed, based on more complex theoretical ideas.…”
Section: Discussionmentioning
confidence: 99%
“…An example of such extended ratio analysis is visualization of energy charge, which was introduced to characterize metabolic energy state using number of phosphorylation sites calculated from abundance of ATP, ADP, and AMP. 36,37) In the near future, various visualizations will be performed, based on more complex theoretical ideas.…”
Section: Discussionmentioning
confidence: 99%
“…We applied MALDI-MSI to mouse skeletal muscle to demonstrate the change in lipid quality that occurs due to acute contraction 16) . In this study, we successfully observed the reduction of diacylglycerol and TAG, which are generally associated with muscle contraction.…”
Section: Application Of Maldi-msi For Lipidsmentioning
confidence: 99%
“…However, it is poorly understood what types of molecular species are changed by muscle contractions due to the complexity and variety of lipid molecular species. In the present study, MALDI-IMS was used to analyze lipid metabolism 19) . Fig.…”
Section: Metabolic Change In Lipids Induced By Contractionmentioning
confidence: 99%